Investigation of treatment efficacy of 10% povidone-iodine sclerotherapy on ovarian cyst diameter: an experimental study - Atilgan, Remzi; Pala, Sehmus; Kuloglu, Tuncay (Tubitak Scientific & Technological Research Council Turkey, 2019)
Background/aim: The purpose of this study was to investigate the effects of 10% povidone-iodine (PI) sclerotherapy on ovarian cyst diameter through an experimental study. Materials and methods: To be able to create ovarian cysts, right unilateral salpingectomy was performed on 20 Wistar albino rats. One month after the operation, the abdomens of all rats were reopened. Sixteen rats with macroscopic ovarian cysts were divided randomly into 2 groups consisting of 8 rats. Group 1 (G1): the cyst content was only aspirated. Group 2 (G2): the ovarian cyst was aspirated and then the cystic cavity was irrigated with PI. Abdomens of all rats were closed and 1 month later they were reopened. Tissues of the right ovaries of the rats were embedded in paraffin blocks for histopathological examination. Follicle count, fibrosis, and congestion were evaluated under a light microscope. Results: For G1, there was no difference in cyst diameters before and after aspiration. In G2, a decrease was observed in cyst diameter. There was no difference in ovarian reserve between the 2 groups. When compared with G1, an increase in fibrosis and congestion was determined in G2. Conclusions: Sclerotherapy into the ovarian cyst for a 5-min period using 10% PI reduces cyst diameter without any change in ovarian reserve.
Keywords: Povidone-iodine; cysts; ovarian reserve; rat